A brief review of our local fringillidae - Powell, Edgar Arthur (My University, 1896)
Introduction: The family of birds known as the Fringillidae belongs to the highest order of birds, the Passeres. It is a family rich in number of species there being about five hundred, representatives of the family are found in every country of the world except Australia. Such a wide distribution of a family is seldom found.
Citation: Powell, Edgar Arthur. A brief review of our local fringillidae. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Fringillidae; Birds; Australia; Passeres; Theses; Manuscripts (documents)